Canadian Critical Luxury Studies Decentring Luxury - Clark, Jessica P.; Lezama, Nigel (Intellect, 2022)
luxury; Canadian fashion; Montreal; Indigenous; production; fashion; history; colonialism; canada; luxury studies; community; consumption